Thermoresponsive Semiconducting Polymer Nanoparticles for Contrast‐Enhanced Photoacoustic Imaging. (19th July 2019) - Cui, Dong; Li, Pengcheng; Zhen, Xu; Li, Jingchao; Jiang, Yuyan; Yu, Aixi; Hu, Xiang; Pu, Kanyi
Abstract: Photoacoustic (PA) agents with biomarker‐activated signals are developed to enhance the signal‐to‐background ratios (SBRs) for in vivo imaging; however, their SBRs still heavily rely on the concentration difference of biomarkers between diseased and normal tissues. By contrast, external stimuli can provide a remote way to noninvasively control the signal generation from the PA agents and in turn enhance SBR, which are less exploited. This study reports the development of thermoresponsive semiconducting polymer brush with poly( N, N ‐dimethylacrylamide)‐r‐(hydroxypropyl acrylate) (PDMA‐r‐HPA) grafts for contrast‐enhanced in vivo imaging. Such a polymer is amphiphilic and can self‐assemble into the nanoparticle (termed as SPNph1) in an aqueous medium, and has lower critical solution temperatures (LCSTs) at 48 °C. Thus, SPNph1 not only has higher photothermal conversion efficiency than the control polymer without PDMA‐r‐HPA grafts, but also can undergo phase separation to form large nanoparticles, leading to enhanced PA signals above LCST. The thermoresponsive PA property of SPNph1 enables in situ remote manipulation of PA signals by photoirradiation to further enhance the tumor SBR. Thus, this study introduces a new generation of organic PA agents with thermoresponsive signal for high‐contrast in vivo imaging. Abstract : Thermoresponsive semiconducting polymer nanoparticles with high photothermal conversion efficiency are developed, enabling remote control of photoacoustic signals by photoirradiation and thus contrast‐enhanced tumor imaging in living mice.